Działalność innowacyjna przedsiębiorstw przemysłu spożywczego w województwie warmińsko-mazurskim - Juchniewicz, Małgorzata (Innovative Activity of Food Industry Enterprises in Warmia and Mazury Voivodeship, 2006)
In the article one characterized innovative activity of food industry companies during years 2000-2004 in Warmia and Mazury province. The analysis shows that expenditures spent on innovation by food industry enterprises are three times bigger than average in firms in region. Also sales value of new and improved products was more than three times bigger than average in province. Among food industry companies especially innovative are these from groups such as: production, manufacture and conservation of meat (151 PKD) and production of milk articles (155 PKD).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 450-457